VIRTUAL EDUCATION IN TEACHING GENERAL PROFESSIONAL SCIENCES TECHNOLOGIES PLACE - Farrukh Murodov (The Conference Hub, 2026)
Advanced technology and programmatic education by means of wide to use big trust that it is being watched to account let’s say, of education modern methods information and communication technologies with integration demand enough. This about developed in countries of students professional competence, including, information technology competence development effective models working exit, interactive education environment organization to grow and to practice of increase didactic guarantee improvement is important importance profession enough.
Keywords: virtual education, training process, virtual didactic tools, diligence environment, information technology competence, virtual education.